(untitled) (Research, Society and Development, 2025)
Tumors of the papilla of Vater, also called ampullomas, represent a rare neoplasm of the digestive tract, but of great clinical importance due to the potential for biliary obstruction and malignant progression. Early diagnosis remains a challenge, given the nonspecific initial symptoms. This article aims to review the main diagnostic and therapeutic aspects, as well as the challenges in the clinical and surgical management of papilla of Vater tumors, offering an updated perspective that will help improve medical practice and develop more effective therapeutic strategies. A narrative literature search was conducted in PubMed, Scielo, and Embase, considering articles published in the last 10 years, as well as classic works on the subject. Publications in English, Spanish, and Portuguese that addressed diagnosis, treatment, and prognosis were included. Diagnosis involves a combination of imaging tests and endoscopic methods, with emphasis on endoscopic ultrasound and endoscopic retrograde cholangiopancreatography (ERCP). The standard treatment for resectable cases is pancreaticoduodenectomy (Whipple procedure), although endoscopic ampullectomy is an option for selected early tumors. Tumor recurrence, surgical complications, and appropriate patient selection still pose challenges. The role of adjuvant therapies remains under investigation, especially in the context of advanced or unresectable tumors. The management of papilla of Vater tumors requires a multidisciplinary approach, combining accurate diagnosis and individualized treatment. Advances in endoscopic and surgical techniques and complementary therapies offer promising prospects, but more robust studies are still needed to standardize approaches.